1993
DOI: 10.1007/bf02536234
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ubiquinone and ubiquinol homologues in rat tissues and subcellular fractions

Abstract: The oxidized (UQox) and reduced (UQred) forms of ubiquinone (UQ) homologues in rat tissues and subcellular fractions were analyzed to elucidate their distribution and physiological role. UQ-9 and UQ-10 were detected in all tissues studied, and UQ-9 was the predominant homologue. The total amount of UQox-10 and UQred-10 was 20-50% that of UQox-9 and UQred-9. The levels of these homologues were highest in heart with lesser amounts occurring in kidney, liver and other organs. In liver and blood plasma, the UQred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 41 publications
2
34
1
1
Order By: Relevance
“…CoQ9 and CoQ10 are widely distributed in the spleen, kidney, heart, liver and plasma. In the liver and plasma, the ratio of reduced CoQ to total CoQ (reduced and oxidized CoQ) is 70-80%, compared to 30% in other tissues (16). The present results did not show any marked differences in serum CoQ9 levels following oral intake of P40 or Q10 oil, and the ratio of reduced CoQ for CoQ9 and CoQ10 was 70-80%.…”
Section: Discussioncontrasting
confidence: 61%
“…CoQ9 and CoQ10 are widely distributed in the spleen, kidney, heart, liver and plasma. In the liver and plasma, the ratio of reduced CoQ to total CoQ (reduced and oxidized CoQ) is 70-80%, compared to 30% in other tissues (16). The present results did not show any marked differences in serum CoQ9 levels following oral intake of P40 or Q10 oil, and the ratio of reduced CoQ for CoQ9 and CoQ10 was 70-80%.…”
Section: Discussioncontrasting
confidence: 61%
“…Because the majority of CoQ 10 is in the quinol form in the cell membranes [10], it can be an effective antioxidant [11]. Many studies on the inhibitory effects of CoQ 10 on lipid peroxidation exist in the literature [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the physiological effects of CoQ10 include the energy through the production of produces ATP with mitochondria activator and the anti-oxidant activity 18,19) . Recently, QH, which is a major CoQ10 in the body, has been put to commercial use and is reported to have such actions as antisenescence activity, which is different from that of oxidized CoQ10 6,11) . This study demonstrated that consumption of QH results in a significant increase in running time.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized CoQ10 is transformed by reduction enzymes into QH (H 2 CoQ10) in the body (especially in the blood plasma and the liver) of animals such as humans and rats, which means that QH is a major metabolic form of CoQ10 11) . As the percentage of QH in the body and the ability to transform oxidized CoQ10 into QH decrease with aging 12) , it has been reported that the action on the body by the consumption of QH has widely different physical effects from that by the consumption of oxidized CoQ10 6) .…”
Section: Introductionmentioning
confidence: 99%